Effect of E-Facture and E-Nofa Implementation on Tax Compliance (A Case Study at KPP Pratama Madya Bekasi) - Triana Yuniati (Kusuma Negara Business School, 2020)
This study aims to analyze the effect of the e-Facture and e-Nofa systems on taxable entrepreneur compliance. This type of research data was obtained from primary data where questionnaires were distributed to taxable entrepreneurs registered at KPP Pratama Madya Bekasi with the incidental sampling method. The research method in this thesis is to use quantitative research methods with a total sample of 90. The results show that (1) the application of the e-Facture system has a positive and significant effect on the compliance of taxable entrepreneurs. (2) The application of the e-Nofa system has a positive and significant effect on Taxable Entrepreneur Compliance. (3) The implementation of e-Facture and e-Nofa has a simultaneous effect on Taxable Entrepreneur Compliance.